Iron-based soft magnetic alloy powder

By adding Al and Ca to the iron-based soft magnetic alloy powder, the shape and surface state are improved, and the problem of difficulty in obtaining high filling rate in low-pressure molding is solved, and magnetic characteristics are improved, and iron-based soft magnetic alloy powder with high flowability and high magnetic characteristics is achieved.

CN111415792BActive Publication Date: 2025-03-11SINTOKOGIO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010010280.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-01-06
Publication Date
2025-03-11
Estimated Expiration
2040-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to obtain iron-based soft magnetic alloy powder with high filling rate in low pressure molding, and its magnetic properties are insufficient.

Method used

By adding Al and Ca to the crystalline iron-based soft magnetic alloy powder, the shape and surface state of the powder are improved, and the specific surface area is reduced, thereby improving fluidity and magnetic properties.

Benefits of technology

It is realized that iron-based soft magnetic alloy powder with high filling rate is obtained in low pressure molding, and its magnetic characteristics are improved, including magnetic permeability and reducing core loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111415792B_ABST
    Figure CN111415792B_ABST
Patent Text Reader

Abstract

The present invention provides an iron-based soft magnetic alloy powder having high fluidity and thus being able to obtain high filling even in a low pressure molding method. A crystalline iron-based soft magnetic alloy powder is provided, which contains 0.5 to 10 weight % Si, 0 to 7 weight % Cr and 0.01 to 1.2 weight % Al, and the remainder is composed of Fe and inevitable impurities. The crystalline iron-based soft magnetic alloy powder may also contain 0.001 to 0.01 weight % Ca.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to iron-based soft magnetic alloy powder. Background Art

[0002] In recent years, as a power inductor used in a power circuit, a soft magnetic material that can be used under high current and high frequency is desired in view of the requirements of miniaturization and low height. In the past, as the main material of the inductor, ferrite-based materials as oxides were used, but because of the low saturation magnetization, it was not conducive to miniaturization. In recent years, the use of metal inductors made of alloy-based materials with high saturation magnetization and conducive to miniaturization and low height has increased rapidly. Soft magnetic alloy powders with iron as the main material are used in metal inductors. It is known that soft magnetic alloy powders and resins are mixed and compressed to obtain powder cores. The magnetic properties of the powder core (saturation magnetization, permeability, core loss, frequency characteristics, etc.) depend on the magnetic properties and particle size distribution, filling properties, and resistance of the soft magnetic alloy powder used.

[0003] As a manufacturing method for metal inductors, powder pressing is usually used. However, in order to obtain a high filling rate during powder pressing, a pressure of up to 300 to 600 MPa needs to be applied. Therefore, the productivity of the pressed powder is low. It is necessary to manufacture metal inductors through a more productive manufacturing method such as transfer molding (injection molding), which is a low-pressure molding method. Therefore, soft magnetic alloy powder with higher fluidity than before is required.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 5354101 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] An object of the present invention is to provide an iron-based soft magnetic alloy powder having high fluidity so as to be highly filled even in a low pressure molding method.

[0009] Technical solutions adopted to solve technical problems

[0010] The inventors of the present invention have conducted various studies and have found that by adding Al to crystalline iron-based soft magnetic alloy powder, surprisingly, the shape and surface state of the iron-based soft magnetic alloy powder are improved and the specific surface area is reduced, thereby improving the fluidity of the powder, achieving high filling even when using a low-pressure molding method, and improving the properties as a magnetic material, thereby ultimately completing the present invention.

[0011] That is, one aspect of the present invention is a crystalline iron-based soft magnetic alloy powder containing 0.5 to 10 wt% Si, 0 to 7 wt% Cr and 0.01 to 1.2 wt% Al, with the remainder being Fe and inevitable impurities.

[0012] According to one embodiment of the present invention, the present invention is a crystalline iron-based soft magnetic alloy powder, which contains 1.5 to 8.5 wt% Si, 0 to 5.0 wt% Cr and 0.01 to 1 wt% Al, and the remainder is composed of Fe and inevitable impurities.

[0013] According to one embodiment of the present invention, there is provided the above-mentioned iron-based soft magnetic alloy powder, wherein a part of Fe is substituted with Ca, and the powder contains 0.001 to 0.01 wt % of Ca.

[0014] According to one embodiment of the present invention, there is provided the above-mentioned iron-based soft magnetic alloy powder, which contains 0.02 to 0.8 wt % of Al.

[0015] According to one embodiment of the present invention, there is provided the above-mentioned iron-based soft magnetic alloy powder, further comprising 0.002 to 0.01 wt % of Ca.

[0016] Another aspect of the present invention is a crystalline iron-based soft magnetic alloy powder having a 100-x- y Si x Cr y (wherein x is 0.5 to 10 wt %, y is 0 to 7 wt %), wherein 0.01 to 1.2 wt % of Al is added relative to 100 wt % of the total amount of the above basic composition.

[0017] According to one embodiment of the present invention, the present invention is a crystalline iron-based soft magnetic alloy powder having a 100-x-y Si x Cr y The basic composition represented by (wherein x is 1.5 to 8.5 wt %, y is 0 to 5.0 wt %) is added with 0.01 to 1 wt % of Al relative to 100 wt % of the total amount of the basic composition.

[0018] According to one embodiment of the present invention, there is provided the above-mentioned iron-based soft magnetic alloy powder, wherein 0.001 to 0.01 wt % of Ca is further added relative to 100 wt % of the total amount of the above-mentioned basic composition.

[0019] According to one embodiment of the present invention, the above-mentioned iron-based soft magnetic alloy powder is provided, and its particle size (D 50 ) is 0.5~150μm.

[0020] According to one embodiment of the present invention, the above-mentioned iron-based soft magnetic alloy powder is provided, and its specific surface area is 1.1m 2 / g or less.

[0021] According to one embodiment of the present invention, there is provided the above-mentioned iron-based soft magnetic alloy powder, wherein the oxygen content thereof is 1.0 wt % or less.

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide an iron-based soft magnetic alloy powder which has high fluidity and can achieve high filling even during low-pressure molding and has high magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope photograph of the iron-based soft magnetic alloy powder of Example 6.

[0025] Figure 2 This is a scanning electron microscope photograph of the iron-based soft magnetic alloy powder of Comparative Example 1.

[0026] Figure 3 This is a graph showing the relationship between the filling rate and the core loss of the iron-based soft magnetic alloy powder of Examples and Comparative Examples. DETAILED DESCRIPTION

[0027] Hereinafter, one embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiments, and appropriate changes can be made within the scope that does not hinder the effects of the present invention. In the following description, "A to B" means "above A and below B".

[0028] The iron-based soft magnetic alloy powder of the present embodiment contains 0.5 to 10 wt%, preferably 1.5 to 8.5 wt% of Si, 0 to 7 wt%, preferably 0 to 5.0 wt% of Cr, 0.01 to 1.2 wt%, preferably 0.01 to 1 wt%, more preferably 0.02 to 0.8 wt% of Al, and the remainder is composed of Fe and inevitable impurities. In addition, in the iron-based soft magnetic alloy powder of the present embodiment, a part of Fe is replaced by Ca, and 0.001 to 0.01 wt%, preferably 0.002 to 0.01 wt% of Ca is contained.

[0029] In this specification, the iron-based soft magnetic alloy powder refers to a conventionally known crystalline soft magnetic alloy powder such as Fe-Si-based, Fe-Si-Cr-based, Fe-Si-Al-based, and Fe-Ni-based.

[0030] With the above composition, the shape and surface state of the iron-based soft magnetic alloy powder are improved, and the specific surface area is reduced. The improvement of the shape and surface state of the iron-based soft magnetic alloy powder means that the iron-based soft magnetic alloy powder becomes closer to a spherical shape, the surface of the iron-based soft magnetic alloy powder has less undulation and becomes smoother, and the fluidity of the iron-based soft magnetic alloy powder is improved by reducing the specific surface area.

[0031] Furthermore, due to the changes in the shape and surface state of the iron-based soft magnetic alloy powder accompanying the reduction of the specific surface area, the magnetic properties of the iron-based soft magnetic alloy powder are improved.

[0032] The iron-based soft magnetic alloy powder of this embodiment has a basic composition represented by Fe 100-x-y Si x Cr y (where x is 0.5 to 10% by weight, preferably 1.5 to 8.5% by weight, and y is 0 to 7% by weight, preferably 0 to 5.0% by weight). Relative to the total amount of 100% by weight of the basic composition, 0.01 to 1.2% by weight, preferably 0.01 to 1% by weight, more preferably 0.02 to 0.8% by weight of Al is added. As described above, in the iron-based soft magnetic alloy powder of this embodiment, by adding 0.001 to 0.01% by weight, preferably 0.002 to 0.01% by weight of Ca relative to the total amount of 100% by weight of the basic composition, a crystalline iron-based soft magnetic alloy powder in which a part of Fe is replaced by Ca is formed.

[0033] <Si (Silicon)>

[0034] The iron-based soft magnetic alloy powder of this embodiment contains 1.5 to 8.5% by weight of Si. Si can reduce magnetostriction in the powder and is beneficial for high magnetic property formation. However, if it exceeds 8.5% by weight, the magnetic flux density will decrease.

[0035] <Cr (Chromium)>

[0036] The iron-based soft magnetic alloy powder of this embodiment contains 0 to 5% by weight, preferably 1.5 to 5% by weight of Cr. Cr has the effect of preventing rust of the powder and increasing the resistivity of the powder, which is beneficial for high magnetic property formation. However, if it exceeds 5.0% by weight, the magnetic flux density will decrease.

[0037] <Al (Aluminum)>

[0038] The iron-based soft magnetic alloy powder of this embodiment contains 0.01 to 1% by weight, preferably 0.02 to 0.8% by weight of Al. By the presence of Al in this range, the shape of the powder can be improved. When it is less than 0.01% by weight, the above effect is small, and when it exceeds 1% by weight, the shape of the powder deteriorates and the magnetic properties are reduced.

[0039] <Calcium (Ca)>

[0040] In the iron-based soft magnetic alloy powder of this embodiment, a part of Fe is replaced by Ca, and it preferably contains 0.001 to 0.01 wt% of Ca, more preferably 0.002 to 0.01 wt% of Ca. By the presence of Ca in this range, the amount of oxygen in the powder can be reduced. When it is less than 0.001 wt%, the above effect is small, and when it exceeds 0.01 wt%, the magnetic properties will be deteriorated.

[0041] When only one of Al or Ca is contained in the iron-based soft magnetic alloy powder, the above effects can also be achieved. However, by containing the two elements Al and Ca in combination, surprisingly, the iron-based soft magnetic alloy powder undergoes a dramatic reduction in specific surface area and a decrease in the amount of oxygen. It is considered that the reason for this result is that due to Al and Ca with high affinity for oxygen, the surface tension of the melt used to manufacture the alloy powder changes, and the amount of oxygen in the melt changes. In addition, if it is an element with high affinity for oxygen similar to Al and Ca, the same effects as Al and Ca can also be achieved.

[0042] <Other elements>

[0043] In the iron-based soft magnetic alloy powder of this embodiment, as inevitable impurities, elements such as N, S, O, etc. can be included within a range that does not affect the target properties.

[0044] The iron-based soft magnetic alloy powder of this embodiment has the effects of reduction in specific surface area and improvement in magnetic properties that are independent of the particle size (D 50 ), but the particle size (D 50 ) is preferably 0.5 to 150 μm. "Particle size" refers to the median particle size D 50 , which can be measured by a conventionally known method, such as the laser diffraction scattering method. The above effects of reduction in specific surface area and improvement in magnetic properties of the iron-based soft magnetic alloy powder can be obtained in iron-based soft magnetic alloy powders with a wide range of particle sizes, but by making the particle size (D 50 ) 0.5 to 150 μm, particularly high effects can be obtained.

[0045] The specific surface area of the iron-based soft magnetic alloy powder of this embodiment is preferably 1.1 m 2 / g or less. The specific surface area can be measured by a conventionally known BET method or the like. By making the specific surface area 1.1 m 2 / g or less, the iron-based soft magnetic alloy powder simultaneously has high fluidity and magnetic properties.

[0046] The oxygen content of the iron-based soft magnetic alloy powder of this embodiment is preferably 1.0 wt% or less. The oxygen content can be measured by the conventionally known combustion-infrared absorption method, etc. By making the oxygen content below 1.0 wt%, the iron-based soft magnetic alloy powder has both high fluidity and magnetic properties.

[0047] [Manufacturing method]

[0048] The iron-based soft magnetic alloy powder of the present embodiment is preferably manufactured by a conventionally known atomization method. For example, Al and Ca are added to a molten material adjusted to a desired composition, and a powder is obtained by an atomization method in which parameters are set to achieve the desired cooling conditions and particle size conditions. The addition of Al and Ca is performed by adding Al and Ca in a metallic form to the molten material, and the order of addition is not limited. However, since Al and Ca are easily converted into oxides, a certain degree of excess Al and Ca needs to be added relative to the target alloy composition.

[0049] Then, the obtained powder is dried and classified, and if necessary, subjected to a coating treatment with a resin or the like, thereby obtaining the target iron-based soft magnetic alloy powder.

[0050] Example

[0051] Examples of the present invention are shown below, but the contents of the present invention should not be interpreted as being limited to these examples.

[0052] [Manufacturing of iron-based soft magnetic alloy powder]

[0053] The materials adjusted to the compositions shown in Tables 1 and 2 were melted in a high-frequency induction furnace and crystalline iron-based soft magnetic alloy powders were obtained by water atomization. The conditions of the water atomization were as follows.

[0054] <Water atomization conditions>

[0055] Water pressure: 100MPa

[0056] Water volume: 100L / min

[0057] Water temperature: 20℃

[0058] Aperture: φ4mm

[0059] Melt temperature: 1800℃

[0060] The obtained iron-based soft magnetic alloy powder was dried using a vibration vacuum dryer [VU-60: manufactured by Chuo Chemical Co., Ltd. (Chuo Chemical)]. The drying method is as follows.

[0061] <Drying conditions>

[0062] Temperature: 100℃

[0063] Pressure: below 10kPa

[0064] Duration: 60 minutes

[0065] The dried iron-based soft magnetic alloy powder was quantitatively analyzed for composition using an ICP emission spectrometer [SPS3500DD: manufactured by Hitachi High-Technologies Corporation], and it was confirmed that the powder had the target composition.

[0066] The target iron-based soft magnetic alloy powder was obtained by classification using an air flow classifier [TURBO CLASSIFIER: manufactured by Nissin Engineering Co., Ltd.]. The particle size (D 50 ).

[0067] The iron-based soft magnetic alloy powder produced as described above was evaluated as follows.

[0068] [Evaluation items]

[0069] 1.Powder physical properties

[0070] 1-1. Shape observation

[0071] The shape of the iron-based soft magnetic alloy powder was observed using a scanning electron microscope (SEM) [JSM7200: manufactured by JEOL Ltd.].

[0072] 1-2. Oxygen content measurement

[0073] The amount of oxygen contained in the iron-based soft magnetic alloy powder was measured using an oxygen analyzer [EMGA823: manufactured by Horiba, Ltd.].

[0074] 1-3. Specific surface area measurement

[0075] The specific surface area of ​​the iron-based soft magnetic alloy powder was measured by the BET method using a specific surface area measuring device [BELSORP-mini: manufactured by Microtrac BEL Co., Ltd.].

[0076] 1-4. Determination of tap density

[0077] In order to evaluate the fluidity of the iron-based soft magnetic alloy powder, the tap density of the iron-based soft magnetic alloy powder was measured using a powder property evaluation device [Powder Tester PT-S: manufactured by Hosokawa Micron Co., Ltd.].

[0078] 2. Magnetic properties (magnetic permeability, core loss measurement)

[0079] Granulated powder is prepared by mixing insulating film soft magnetic alloy powder and epoxy resin. The granulated powder is pressed and molded (molding pressure: 5 MPa) into a ring shape to produce a pressed powder core (outer diameter: 15 mm, inner diameter: 9 mm, thickness: 3 mm). A toroidal core is prepared by double-winding a copper wire with a wire diameter of 0.3 mm and used as an evaluation sample.

[0080] The magnetic permeability and core loss were measured using a BH analyzer [SY8258: manufactured by Iwatsu Instruments Co., Ltd.] under the conditions of a measurement frequency of 1 MHz and a maximum magnetic flux density of 25 mT.

[0081] Furthermore, using the insulating film soft magnetic alloy powders having the compositions of Comparative Example 1 and Example 4 in Table 1, a plurality of powder cores having different filling rates were prepared by adjusting the compacting pressure, and toroidal cores were prepared as described above, and the core loss was measured.

[0082] [Evaluation results]

[0083] The evaluation results are shown in Tables 1 and 2. In addition, in the "Powder Flow Evaluation" in Table 1, relative to the measured value of the tap density of the comparative materials (Comparative Example 1 in the case of Comparative Examples 2-4 and Examples 1-11, Comparative Example 5 in the case of Example 12, Comparative Example 6 in the case of Comparative Examples 7-9 and Examples 15-25, Comparative Example 10 in the case of Example 26, Comparative Example 11 in the case of Comparative Examples 12-14 and Examples 29-39, Comparative Example 15 in the case of Example 40, Comparative Example 16 in the case of Examples 43-45, Comparative Example 17 in the case of Examples 46-48, Comparative Example 18 in the case of Example 49, and Comparative Example 19 in the case of Example 50) to which both Al and Ca were not added and which had the same composition and particle size, an increase in the measured value of the tap density was recorded as × when it was less than 10%, Δ when it was 10% or more and less than 20%, and 0 when it was 20% or more. In addition, the "Magnetic Property Evaluation" in Tables 1 and 2 is also the same. Relative to the measured values ​​of core loss of comparative materials to which Al and Ca are not added (Comparison Example 1 for Comparison Examples 2-4 and Examples 1-11, Comparison Example 5 for Example 12, Comparison Example 6 for Comparison Examples 6-9 and Examples 15-25, Comparison Example 10 for Example 26, Comparison Example 11 for Comparison Examples 12-14 and Examples 29-39, Comparison Example 15 for Example 40, Comparison Example 16 for Examples 43-45, Comparison Example 17 for Examples 46-48, Comparison Example 18 for Example 49, and Comparison Example 19 for Example 50), the measured value of core loss is recorded as × when the measured value of core loss decreases by less than 20%, as Δ when it is greater than 20% and less than 30%, and as 0 when it is greater than 30%.

[0084] In the case of Examples 13, 14, 27, 28, 41, and 42, the measured values ​​of the tap density and the core loss were evaluated in the same manner with respect to the comparative materials (Comparative Examples 1, 6, 11, 16, and 17) having the same particle size.

[0085] [Table 1]

[0086]

[0087] [Table 2]

[0088]

[0089] As shown in Table 1 and Table 2, the iron-based soft magnetic alloy powder of the embodiment has lower measured values ​​of oxygen content and specific surface area and improved fluidity as powder properties compared with the comparative material of the comparative example. That is, by adding Al to the crystalline iron-based soft magnetic alloy powder, the iron-based soft magnetic alloy powder of the present invention has high fluidity.

[0090] Furthermore, the magnetic properties of the iron-based soft magnetic alloy powder to which Ca is added are that the magnetic permeability is improved and the core loss is greatly reduced. That is, the iron-based soft magnetic alloy powder of the present invention has both high fluidity and magnetic properties.

[0091] In addition, the iron-based soft magnetic alloy powder of the present invention has a particle size D as shown in Examples 12, 26, 40 and 50. 50 The particle size is as large as 13 μm or 150 μm, or the particle size D shown in Example 49. 50 Even with a particle size as small as 0.5 μm, both high fluidity and magnetic properties are achieved. That is, it is found that the effect of adding Al and Ca, which is a characteristic of the present invention, does not depend on the particle size of the iron-based soft magnetic alloy powder.

[0092] In addition, as shown in Examples 13, 14, 27, 28 and 41-50, it can be seen that the present invention can also impart high fluidity and magnetic properties if it is a crystalline iron-based soft magnetic alloy. That is, even if it is a crystalline soft magnetic alloy powder such as Fe-Si-Al system, Fe-Ni system, etc., the same effect as shown in the examples of the present application can be obtained.

[0093] As can be seen from the results shown in Tables 1 and 2, the iron-based soft magnetic alloy powder of the present invention has both high fluidity and magnetic properties and therefore has excellent properties as a material for powder compacting of various electronic components.

[0094] Figure 1 is a scanning electron microscope photograph of the iron-based soft magnetic alloy powder of Example 6, Figure 2 This is a scanning electron microscope photograph of the iron-based soft magnetic alloy powder containing no Al and Ca of Comparative Example 1.

[0095] from Figure 1 and Figure 2 It can be seen that Figure 1 Iron-based soft magnetic alloy powder and Figure 2 Compared with the iron-based soft magnetic alloy powder, the shape is obviously spherical, the surface is less undulating and smooth, and has a significantly different shape. The improvement in the powder properties and magnetic properties shown in Table 1 can be attributed to the Figure 1 The changes in shape and surface condition are shown.

[0096] in addition, Figure 1Although not shown in the figure, the shape and surface condition of the powder with a larger particle size as the classified coarse powder are also improved.

[0097] like Figure 3 As shown, the annular magnetic core made of the iron-based soft magnetic alloy powder containing Al and Ca in the embodiment has a significantly reduced core loss in a wide range of filling rates compared to the annular magnetic core made of the iron-based soft magnetic alloy powder not containing Al and Ca in the comparative example. That is, the iron-based soft magnetic alloy powder of the present invention has excellent magnetic properties and has excellent properties as a material for powder molding of various electronic components.

Claims

1. A crystalline iron-based soft magnetic alloy powder, comprising 0.5 to 10 wt% Si, 0 to 7 wt% Cr and 0.01 to 1.2 wt% Al, the remainder being Fe and unavoidable impurities, a part of the Fe being replaced by Ca, and comprising 0.001 to 0.01 wt% Ca.

2. The crystalline iron-based soft magnetic alloy powder according to claim 1, comprising 1.5 to 8.5 wt% Si, 0 to 5.0 wt% Cr and 0.01 to 1 wt% Al, with the remainder being Fe and unavoidable impurities.

3. The crystalline iron-based soft magnetic alloy powder according to claim 1 or 2, characterized in that: Contains 0.02 to 0.8 wt% of Al.

4. The crystalline iron-based soft magnetic alloy powder according to claim 3, characterized in that Contains 0.002 to 0.01 wt% of Ca.

5. A crystalline iron-based soft magnetic alloy powder having Fe 100-x-y Si x Cr y The basic composition represented by x is 0.5-10 wt.%, y is 0-7 wt.%, 0.01-1.2 wt.% Al is added relative to the total amount of 100 wt.% of the basic composition, and 0.001-0.01 wt.% Ca is also added relative to the total amount of 100 wt.% of the basic composition.

6. The crystalline iron-based soft magnetic alloy powder according to claim 5, which has Fe 100-x-y Si x Cr y The basic composition represented by the invention is that x is 1.5 to 8.5 wt %, y is 0 to 5.0 wt % and 0.01 to 1 wt % of Al is added relative to 100 wt % of the total amount of the basic composition.

7. The crystalline iron-based soft magnetic alloy powder according to any one of claims 1 to 6, characterized in that Particle size D 50 0.5~150μm.

8. The crystalline iron-based soft magnetic alloy powder according to any one of claims 1 to 7, characterized in that Specific surface area: 1.1m 2 / g or less.

9. The crystalline iron-based soft magnetic alloy powder according to any one of claims 1 to 8, characterized in that The oxygen content is less than 1.0 wt%.

Citation Information

Patent Citations

  • Soft magnetic powder, dust magnetic core, magnetic part, and method for producing dust magnetic core

    CN108883465A

  • Powder for powder-compact magnetic core

    JP2018182040A